Influence of Height Waterlogging on Soil Physical Properties of Potential and Actual Acid Sulphate Soils - Fahmi, Arifin; Susilawati, Ani; Rachman, Ahmad (JOURNAL OF TROPICAL SOILS, 2014)
Water management is main factor that determines the successful of rice cultivation in acid sulphate soil. Soil waterlogging determines the direction and rate of chemical, geochemical and biological reaction in the soil, indirectly these reactions may influence to the changes of soil psycal properties during soil waterlogging process. The experiment was aimed to study the changes of two type of acid sulphate soils physical properties during rice straw decomposition processes.  The  research  was  conducted  in  the  greenhouse  consisting  of  the  three  treatment  factors  using  the completely randomized design with three replications. The first factor was soil type: potential acid sulphate soil (PASS) and actual acid sulphate soil (AASS). The second factor was height of water waterlogging: 0.5-1.0 cm (muddy water–level  condition) and 4.0 cm from above the soil surface (waterlogged). The third factor was organic matter type: rice straw (RS), purun tikus (Eleocharis dulcis) (PT) and mixed of RS and PT (MX). Soil physical properties such as aggregate stability, total soil porosity, soil permeability, soil particle density and bulk density were observed at the end of experiment (vegetative maximum stage). The results showed that acid sulphate soil type had large effect on soil physicl properties, soil waterlogging decreased aggregate stability, soil particle density and bulk density both of soil type.Keywords : Acid sulphate soils, soil physical properties, and waterlogging [How to Cite: Arifin F, A Susilawati and A Rachman. 2014. Influence of Height Waterlogging on Soil Physical Properties of Potential and Actual Acid Sulphate Soils. J Trop Soils 19(2): 77-83. Doi: 10.5400/jts.2014.19.2.77]